The Relationship between Self Efficacy and Family Social Support on the Psychological Well-Being of Honorary Teachers - Yoana Elvita Fetriana; Lucia Hernawati (Eduvest - Journal of Universal Studies, 2026)
The precarious employment status and inadequate welfare of honorary teachers in Indonesia potentially undermine their psychological well-being, which is crucial for educational quality. This study aims to investigate the relationship between self-efficacy and family social support with the psychological well-being of honorary teachers. A correlational quantitative research design was employed, utilizing a population study technique. The entire population of 60 honorary teachers from an educational foundation in Semarang City, with a minimum of two years of service, participated as the sample. Data were collected using three adapted scales: the Ryff’s Psychological Well-Being Scale (RSPWB), the Generalized Self-Efficacy Scale (GSES), and a family social support scale, all of which demonstrated high reliability (Cronbach’s alpha > 0.9). Multiple linear regression analysis was used for data analysis. The results revealed that self-efficacy and family social support together had a significant positive correlation with the psychological well-being of honorary teachers (R = 0.618, p < 0.01), contributing 38.2% to its variance. Partially, both self-efficacy (β = 0.336, p < 0.05) and family social support (β = 0.343, p < 0.05) were significant positive predictors. The findings imply that strengthening teachers’ self-belief in their capabilities and fostering a supportive family environment are crucial strategies for enhancing their psychological well-being. This study underscores the need for policies that not only address the economic welfare of honorary teachers but also consider psychosocial interventions.